Effect Analysis of Loudspeaker’s Placement Angle and Direction on Frequency Response and Sound Pressure Level in TV Applications - DEMIREL, Ibrahim (Archives of Acoustics, 2021)
In a television, obtaining a good acoustic response is a challenging issue because of slim mechanical structures. The area dedicated for speaker’s placement is limited and inadequate space inside the cabinet of a TV prevents possible solutions to increase the sound performance. In addition, frame of the TV’s is getting narrower as the customers searching for the highest screen to body ratio. These designing aspects restrain optimal speaker positioning to achieve good sound performance. In this paper, an analysis related to speaker’s placement and mounting angle is proposed. A rotation setup compatible with a TV was prepared to measure different facing position of the speaker. This paper proposes the analysis of speaker’s rotation and facing direction in a flat panel television and its effects on sound pressure level together with deviation of the acoustic response. Measurement results are analyzed with an audio analyzer together with a statistics tool to achieve precise results.